2017
DOI: 10.21511/imfi.14(2-1).2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Ownership structure and corporate performance: evidence from property and real estate public companies in Indonesia

Abstract: This paper has proposed a specific case in the property and real estate sector regarding the impact of ownership structure and corporate performance, since this sector is one of those with booming investment in Indonesia. The ownership structure was represented by the institutional investor and managerial ownership, and the Economic Value Added (EVA) and Tobin's Q were used as a proxy for firm performance. This study utilized the purposive sampling of 240 observations over the period 2010-2015. The fixed and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
1
13
0
4
Order By: Relevance
“…For the last hypothesis in this model found to be rejected and the alternative hypothesis is accepted which stated that there is a negative relationship between institutional ownership and earnings per share. The present result is in line with previous empirical studies results like (Saleh et al, 2017;Ahmad et al, 2019).…”
supporting
confidence: 94%
See 1 more Smart Citation
“…For the last hypothesis in this model found to be rejected and the alternative hypothesis is accepted which stated that there is a negative relationship between institutional ownership and earnings per share. The present result is in line with previous empirical studies results like (Saleh et al, 2017;Ahmad et al, 2019).…”
supporting
confidence: 94%
“…Therefore, institutional ownership may lead firms to have a high financial performance as consequences of a high quality of management, various opportunities and resources available, and ability to monitor these firms, also a good experiences on how to reduce others stockholders expenses (Rose, 2014). However, the findings of previous empirical studies were be inconsistency where some found a positive relationship among institutional ownership and firms' financial performance, among these studies (Haija and Alrabba, 2017;Koji, et al, 2020).Whereas, (Charfeddine and Elmarzougui, 2011;Rose, 2014, Saleh et al, 2017Ahmad et al, 2019) found a negative association between institutional ownership and financial performance in their studies. On this basis, the following hypothesis was formulated: H3: there is a positive relationship between institutional ownership and Bahrain commercial banks performance.…”
Section: Institutional Ownershipmentioning
confidence: 88%
“…A significant positive relationship between institutional ownership and performance of 73 listed firms in Egypt from 2007 to 2014 was reported by (Masry, 2016). In Indonesia, Saleh, Zahirdin, & Octaviani (2017) sampled property and real estate public companies to assess the relationship between ownership structure and firm performance. Contrary to the partially significant effect of managerial ownership, institutional ownership was found to have a significant effect on firm performance.…”
Section: Relationship Between Institutional Ownership and Financial Performancementioning
confidence: 99%
“…This study adopted Tobin's q formula as modified by Chung and Pruitt (1994) to measure financial performance indicators (Phung & Mishra, 2016); (Manyuru et al, 2017); (Saleh et al, 2017). As the first independent variable, institutional ownership was measured following the approach by (Saleh et al, 2017) who measured institutional ownership as the percentage of shares owned by institutional investors from both financial and non-financial organizations. Secondly, foreign ownership was based on the percentage of shares owned by non-citizens or foreign investors (Ongore, 2011); (Hintošová & Kubíková, 2016).…”
Section: Measurement Of Variablesmentioning
confidence: 99%
“…In tandem with (Saleh, Zahirdin, & Octaviani, 2017), institutional ownership comprised of the percentage of shares owned by institutional investors from both financial and nonfinancial organizations. Foreign ownership, on the other hand, was determined using the percentage of shares owned by foreign investors (Ongore, 2011); (Hintošová & Kubíková, 2016).…”
Section: Measurement Of Variablesmentioning
confidence: 99%